Information needs among women taking part in primary HPV screening in England: a content analysis. Issue 12 (15th December 2020) - Marlow, Laura; Forster, Alice S; McBride, Emily; Rockliffe, Lauren; Kitchener, Henry; Waller, Jo
Abstract : Objectives: Introducing primary human papillomavirus (HPV) testing to cervical screening programmes means changes to the results women receive. We explored additional information needs among women undergoing HPV primary screening. Design: Women were sent a postal questionnaire shortly after receiving their results and 6 and 12 months later. Each questionnaire asked if women had any unanswered questions about cervical screening or HPV testing. Free-text responses constituted the data. Themes were identified using content analysis. Setting: National Health Service (NHS) Cervical Screening Programme, England. Participants: 381 women who recorded one or more free-text responses. Results: The most common theme represented women's emotional responses and attempts to understand their results. This theme was raised by 45% of women overall, but was as high as 59% in the HPV cleared group. General questions about the cause and epidemiology of HPV were raised by 38% of women and were more common among those testing HPV positive with normal cytology (52%). Questions about the purpose and procedure for HPV testing were most common among HPV-negative women (40%, compared with 16%–24% of the other results groups). Questions about future implications of test results were raised by 19% of women, and this theme was most common among those with persistent HPV. Conclusions: Despite provision of information alongside screening invitations, women can still have unanswered questions following receipt of their results. Details about the epidemiology of HPV and why cervical screening procedures are changing should be included with screening invitations. Some results groups may benefit from additional tailored information with their results letter.